Correlation Between Blood Glucose Control And Decrease Of Peripheral Vascularization In Diabetes Mellitus Patient - Fitria Endah Janitra; Dinda Sandika (NURSCOPE: Jurnal Penelitian dan Pemikiran Ilmiah Keperawatan, 2018)
Introduction: Diabetes mellitus (DM) is a metabolic disorder characterized by elevated blood glucose levels. Chronic complications of DM affect coronary circulation, peripheral vascularization, and blood vessels of the brain. Decrease in peripheral vascularization increases the risk of tissue ischemia and weakens functional status, therefore it is necessary to control blood glucose levels. Islam teaches to its believers to control their diet, where diet is one of the four pillars of diabetes management. Methodology: this is analytic descriptive research with cross sectional methods in 67 respondents taken by consecutive sampling technique. Results: There was a significant correlation within blood glucose control and decreased peripheral vascularization in DM patients (p-value 0.010). Discussion: need further research regarding nursing intervention to control blood glucose.